Advance care planning (ACP) to promote receipt of value-concordant care: Results vary according to patient priorities. - Holly G Prigerson; Martin Viola; Paul K Maciejewski; Francesca Falzarano (PLoS ONE)
Background Benefits of advance care planning (ACP) have recently been questioned by experts, but ACP is comprised of discrete activities. Little is known about which, if any, ACP activities are associated with patients' greater likelihood of receiving value-concordant end-of-life (EoL) care. Objectives To determine which ACP activities [Do-Not-Resuscitate (DNR) order completion, designation of a healthcare proxy (HCP), and/or EoL discussions with physicians], individually and in combination, are associated with the greatest likelihood of receiving value-concordant care, and how results may vary based on patient-reported EoL care priorities. Methods Data from 2 federally-funded, multisite, prospective cohort studies of EoL cancer care from 2002-2019 were analyzed. Cancer patients (N = 278) with metastatic disease refractory to chemotherapy were interviewed for a baseline assessment and followed prospectively until death. Interviews regarding patient priorities occurred a median of 111 days prior to death; data regarding EoL medical care were collected post-mortem from caregiver interviews and medical record abstraction. Patients who 1) prioritized life-extending care, and then received life-extending care (or avoided hospice care), or 2) prioritized comfort-focused care, and then avoided life-extending care (or received hospice care) in the last week of life, were coded as receiving value-concordant care. Results After inverse propensity score weighting, the ACP combination associated with the largest proportion of patients receiving value-concordant care was DNR, HCP, and EoL discussions (87% vs. 64% for no ACP activities; OR = 3.91, p = 0.006). In weighted analyses examining each ACP activity individually, DNR orders were associated with decreased likelihood of life-extending care (89% vs. 75%; p = 0.005) and EoL discussions were associated with increased likelihood of hospice care (77% vs. 55%; p = 0.002) among patients prioritizing comfort. ACP activities were not significantly associated with increased likelihood of receiving value-concordant care among patients prioritizing life-extension. Conclusions and relevance For patients who prioritize comfort, EoL discussions with physicians and completion of DNR orders may improve odds of receiving value-concordant EoL care. For patients who prioritize life-extension, ACP does not appear to improve odds of receiving value-concordant EoL care.